Pertumbuhan Dan Kandungan Vitamin C Tanaman Kangkung Darat (Ipomoea reptans Poir) Pada Media Zeolit Dengan Penambahan Asam Humat - Adhelia Syefanis; Elly Proklamasiningsih; Iman Budisantoso (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2019)
Ipomoea reptans Poir is the most favoured vegetable that mostly known by the people because in addition having good nutrition content, it is one type of vitamin C good source other than fruits. Vitamin C is an antioxidant which is required by the body to maintain the immune of body from the damaging effect of free radicals. The addition of organic compound in the form of humic acid that has a complex structure with high molecular weight and contains an active group that can increase the growth and productivity of plants. The high availability of nutrients require a carrier such as zeolite. Zeolite is a silicate mineral which have a high cation exchange capacity (CEC) (varying between 80-180 meq/100g). The addition of zeolite as a carrier is expected to increase the production of food crops such as corn. This study aimed to know the effect of humic acid with zeolite growth media for the growth and vitamin C content in Ipomoea reptans Poir and also and to determine the concentration of humic acid that most effect to the growth and vitamin C content in Ipomoea reptans Poir. The research was conducted at the Laboratory of Plant Physiology and Greenhouse, Faculty of Biology, Jenderal Soedirman University, Purwokerto by using experimental methods. The research was conducted from January 2019 to March 2019 with using completely randomized design (CRD). The parameters were observed in this study are the number of leaves, plant fresh weight, dry weight of plants, and vitamin C content. The data were analyzed by analysis of variance at the level of 95% and 99%, then following by analytical analysis BNT 95%. The results of this research showed that the addition of humic acid with a concentration of 4 g.kg-1 zeolite growing media can increase Ipomoea reptans Poir growth and the addition of humic acid to the zeolite growth media cannot increase the vitamin C content of Ipomoea reptans Poir.